And yet, we were modern. The paradoxes of Iberian science after the Grand Narratives. (June 2017) - Pimentel, Juan; Pardo-Tomás, José
In this article, we try to explain the origin of a disagreement; the sort that often arises when the subject is the history of early modern Spanish science. In the decades between 1970 and 1990, while some historians were trying to include Spain in the grand narrative of the rise of modern science, the very historical category of the Scientific Revolution was beginning to be dismantled. It could be said that Spaniards were boarding the flagship of modern science right before it sank. To understand this décalage it would be helpful to recall the role of the history of science during the years after the Franco dictatorship and Spain's transition to democracy. It was a discipline useful for putting behind us the Black Legend and Spanish exceptionalism.